PERAN KUALITAS DAN PENGALAMAN DALAM MEMBANGUN LOYALITAS PELANGGAN GRANDLUCKY SUPERSTORE - Galuh Mira Saktiana; Sylven Siurensia (Universitas Muhammadiyah Metro, 2026)
This study investigates how service quality and customer experience contribute to customer loyalty, with satisfaction functioning as a mediating variable at GrandLucky Superstore in Jakarta. A quantitative approach was employed by distributing an online questionnaire to 227 individuals who had made at least two purchase transactions at GrandLucky. Respondents were selected using purposive sampling, and the data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique. The results indicate that both service quality and customer experience exert significant and positive effects on customer satisfaction, which in turn strongly influences loyalty. The analysis also confirms that satisfaction serves as a key mediator linking service quality and customer experience to loyalty. These findings suggest that improved service performance and more engaging shopping experiences strengthen customers’ commitment to continuing their patronage of GrandLucky. From a managerial perspective, maintaining consistent service delivery, enhancing pleasant interactions, and managing positive shopping experiences are essential strategies for fostering long-term customer relationships and reinforcing competitive advantage in the premium retail sector.